Study Regarding Calves Health Practice from Birth to Weaning on Romanian Dairy Buffalo Farms, Considering Farm Size - Elena Raducanu; Roxana Elena Stefan (Vasiliu); Remus Ioan Chiorean; Livia Vidu (Scientific Papers Animal Science and Biotechnologies)
This study explores the health management practices applied to dairy buffalo calves in Romania from birth to weaning, with a focus on preventive strategies and main disease occurrence in relation to farm size. The data were collected through a structured questionnaire distributed among a limited number of Romanian dairy buffalo farms, reflecting the relatively low national prevalence of this farming system. The most commonly reported preventive methods against technopathies included vitamin and selenium supplementation as well as environmental condition adjustments. However, due to the small sample size, the availability of comprehensive statistical data was limited. Preventive vaccination was not widely practiced among buffalo farmers. Large-scale farms reported the use of vaccines, small farms did not apply vaccination at all, indicating a gap in biosecurity and preventive care. Regarding disease occurrence, the incidence of renal disorders, diarrhoea, and respiratory diseases among buffalo calves remained consistently low, below 5%, and showed no significant variation based on farm size. These findings suggest that while certain basic health practices are implemented, more structured preventive programs could benefit the overall health outcomes of buffalo calves, particularly in smaller farms where preventive measures are minimal or absent.